디지털 시대의 리더십 융합: 디지털 과업중심 리더십과 분산적 리더십이 혁신적 행동에 미치는 영향 - 민선정; 김태진; 강주영 (인터넷전자상거래연구, 2025)
In the era of accelerated digital transformation, leaders are akin to conductors who must consider the generational characteristics of their workforce to drive organizational innovation. However, there remains a significant gap in research regarding the interactions between different leadership styles and innovative behaviors in the digital age. This lack of study leaves a crucial void in the development of effective innovation strategies for organizations. This study analyzes the interaction effects of distributed leadership and digital task-centered leadership, along with the mediating effects of the MZ generation's regulatory focus. Utilizing a 2*2 scenario-based experimental method with 344 MZ generation participants, the findings reveal that both digital task-centered leadership and distributed leadership independently influence innovative behavior. The study highlights the mediating effects of promotion focus and prevention focus among MZ generation employees. However, the interaction effect between the two leadership styles was not significant. These results suggest that in digital environments, organizations should adopt differentiated leadership strategies tailored to their specific contexts rather than relying on a high level of complementary leadership fusion.
Keywords: Digital Task-Centered Leadership; Distributed Leadership; Innovative Behavior; LMX; Promotion Focus; Prevention Focus; Scenario Experimental Method.